STATUS PEMBAGIAN GAJI PEGAWAI NEGERI SIPIL PADA MANTAN ISTRI DALAM PANDANGAN HUKUM ISLAM - Nurul Azidah (MIYAH : Jurnal Studi Islam, 2020)
Abstract: The Government considers that citizens of Indonesia who have the status of civil servants as state apparatuses have specialities from other Indonesian citizens, so that required a separate rule. So on April 21, 1983 issued Government Regulation (PP) no. 10 years 1983 Jo. Government Regulation No.45 of 1990 on Marriage and Divorce Licenses for Civil Servants specifically regulating marriage and divorce permits for Civil Servants In other words, this regulation is an exception to law at year 1974 Regarding marriage permits, divorce, between the rules is the salary division rules for civil servants wife after the divorce until the wife remarried. The type of research in this thesis is literature research and the method used is descriptive analysis with qualitative approach the researcher. The status of civil servants salary to be given to his ex-wife belongs to the income of iddah when the wife is still living the period of iddah And not including the concept of livelihood madliyah, mut'ah also grant as the concept offered by fuqoha’.Keywords: Salary Distribution, Civil Servant, Islamic Law, Compilation of Islamic Law